Red sandstone panel depicting musicians and dancers - Temples of India Project Team (Jio Institute, 2024)
A red sandstone panel with various segments separated by pillarlets, with various musicians and dancers placed in each panel, is affixed on the platform of the 18th century CE Shiva Temple.